OCA theory and EMU Eastern enlargement: An empirical application - Marco Weimann (Deutsche Bank Research, 2003)
The accession of several Central and Eastern European Countries to Euroland is likely to be realised within the next years. Some studies aim at analysing the suitability of these Euro aspirants for currency union with EMU by evaluating the related macroeconomic costs. Still, they are prone to the Lucas critique since they do not consider endogeneity of the relevant criteria. We build on methodologies developed with regard to the theory of optimum currency areas in the context of present EMU and use a structural VAR approach to evaluate EMU suitability of the candidate countries. To correct for the widespread flaw of previous studies we use lagged time series to account for endogeneities. An evaluation of the changing country characteristics within the process of integration in Western Europe confirms the importance of this approach.
Keywords: E42; F33; F36; 330; OCA; EMU; shock analysis; Eastern enlargement; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Optimaler Währungsraum; Schock; Wirtschaftliche Anpassung; Schätzung; Osteuropa